Mixed practices including use of ideas from narrative therapy with a woman with diagnosis of an intellectual disability and personality disorder. Issue 5 (5th September 2017) - El-Tahir, Mohamed Omer; Bayley, Amanda
Abstract : Purpose: The purpose of this paper is to present outcomes of mixed practices including use of ideas from narrative therapy (NT) in a case of mild intellectual disability (ID) and personality disorder. The formulation, therapy adaptation and outcomes are presented. Design/methodology/approach: The study is a single case report describing patient presentation, assessments, psychological formulation and the mixed interventions approaches used, including ideas from NT. Adaptations to meet the needs of patients with ID were described, and therapy outcome measured using Health of the Nation Outcome scale and Psychiatric Assessment Schedule for Adults with Developmental Disorders was presented. Findings: The ideas used from NT suggest this is potentially a useful approach in practice for people with intellectual disabilities and personality disorder. However, adaptation is needed for it to be used successfully in practice as a therapeutic intervention. Research limitations/implications: A single case study has its limitations, and further work on using ideas from NT, its adaptation and use in this population will be needed. Originality/value: There is no previous case of use of NT among patients with ID and personality disorder.